Identifying and Regulating the Environmental Risks in the Development and Utilization of Natural Gas as a Low-Carbon Energy Source - Fu, Jiaxin; Liu, Yingqi; Sun, FeiHong (Frontiers in Energy Research, 2021)
In response to climate change and energy transition, natural gas has been rapidly developed as a relatively low-carbon energy source by many countries. However, there remain environmental risks at different stages in the entire process from exploitation to utilization. Firstly, this article identifies various environmental risks and benefits of natural gas along the entire industry chain from upstream exploitation and midstream transportation to downstream utilization. It is found that, during upstream exploitation, hydraulic fracturing has the worst environmental impact. During the midstream storage and transportation stage, methane leakage is the biggest environmental risk. In the downstream combustion and utilization stage, the risk to environment is less than other energy sources, although there are some greenhouse gas effects and water pollution issues. Thus, this article puts forward some policy recommendations for different stages from exploitation to utilization. In the upstream stage, especially hydraulic fracturing activity, we suggest strengthening environmental assessment management, improving policy standards, creating a water quality monitoring plan, and promoting the innovation of key technologies. In terms of the midstream, besides pipeline laying and site selection, we focus on monitoring the system, including leak detection, quality management of engineering materials, and risk identification and management. When it comes to the downstream, we encourage the application of advanced technologies to improve thermal efficiency and reduce emissions, such as gas-fired related technologies, natural gas recycling technologies, distributed energy technologies, and green and low-carbon service technologies.